Ahkam Tashorruf fi Amwal Yatama Fi Hadhonatim Wa Tathbiqotuha Fi Ma'had Ibnu Taimiyah Bogor - Suryana, Suri, Dr. M. Mu'inudinillah Basri, M. A, Dr. Rosyid Bin Abdul Mun'im Ar-Rojjal (2017)
It is shown in society, that a lot of orphange become cheated by some people called a Thug. Orphanage have been used by a thug just how to get a fortune or to get money. The thug forcedthe orphanage to become street begger, and the orphange received small amounth of money just bearly enough to fill their stomach. This thesis entitled "Legal to Use Hidden the wealth of young orphaned in his custody and its implementation in Islamic Boarding School OrphaneIbnuTaimiyah, Bogor, West Java". The thesis written by SuriSuryana one of the Graduate Student Faculty of Shariah Department of Fiqh and UshulFiqhMuhammadiyah University of Surakarta (UMS) Solo. This thesis describes Shari'a Law Review how in using the wealth of the young orphanage. This thesis writing method is using an inductive approach , analysis approach , and practical approach. Researchers collect scientific materials of Islamic books and studying it, and conduct field study in Islamic Boarding School OrphaneIbnuTaimiyah, Bogor, West Java. It can be concluded that the guardians of orphans may use/action against an orphan's property fosterage in two circumstances. State of first instance before puberty and the second after puberty. The action taken by the trustee was not yet of age when his fatherless orphans then the property is use for the purposed of orphan itself, in the form of food, clothing and a decent education, as well as taking into account the scale priority : primary, secondary and stersier, But when orphaned was already of age, the trustee shall submit his entire to the orphane. For management institutions orphaned young children may use their wealth by paying attention to welfare benefits and avoid the occurrence of damages and keep the five basic needs and take into account the scale of priorities. In addition, should the agency managing young orphan invested with various types of business after taking into account the advantages and disadvantages. Islamic Boarding School OrphaneIbnuTaimiyah, Bogor, West Java trying to implementation Shari'a Laws in the management of the fund of orphans by paying attention to welfare and avoid the occurrence of the damages and keep the five basic needs and take into account the scale of priorities. Core words in this thesis are : Law, Action/Manage, Orphans, Implementation, and Parenting Institute Islamic Boarding School OrphaneIbnuTaimiyah.